Elements of Augmented Reality Application Design in Teaching and Learning Process - Zuraida Mohd Nor, Fadila; Ab Halim, Fazlinda (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the purpose is to identify the elements of augmented reality (AR) application design for the analysis phase to develop an AR application. Information and communication technology has acquired numerous advantages in all areas of organization in every country, such as in the education field. AR applications have been utilized in many fields, such as innovation using technology for the teaching and learning process, but there is still a lack of knowledge, skills, and devices in their operation. AR is an application that consolidates virtual objects and real objects in real life to attract students using AR applications. AR application utilizing fascinating introduction systems using interesting presentation techniques such as displaying 3D objects, audio, video, and animation by simply scanning the smartphone camera towards a particular picture that has been structured. Therefore, the methodology research is based on past reading and literature studies by using document analysis. At the end of the study, several main elements were found in this research, which are multimedia, device, student, and social elements that can be used in the design phase analysis of AR applications.